2007
DOI: 10.1002/bem.20369
|View full text |Cite
|
Sign up to set email alerts
|

Mobile telephone use effects on peripheral audiovestibular function: A case–control study

Abstract: Low level radio-frequency (RF) signals may produce disorientation, headache and nausea. This double blind study tested nine case-subjects, who complained of various symptoms after prolonged mobile telephone use and 21 control subjects. Each subject underwent a series of trials, in which a dummy mobile telephone exposure system was held to each ear for 30 min in (a) pulsed, (b) continuous RF emission or, (c) no emission test modes. In the active pulsed and continuous modes the same mean power as the output of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
0
22
2
1
Order By: Relevance
“…In three studies, one using 60 Hz exposure [Lyskov et al, 2001] and two using mobile phonelike exposure [Wilén et al, 2006;Bamiou et al, 2008], no effects of EMF exposure were detected on brain physiology, and the visual, auditory and balance systems (Table 6). With the exception of critical flicker fusion frequency, which was recorded in two studies, each of the other endpoints was tested in only one study.…”
Section: Brain Physiology and The Sensory Systemmentioning
confidence: 99%
“…In three studies, one using 60 Hz exposure [Lyskov et al, 2001] and two using mobile phonelike exposure [Wilén et al, 2006;Bamiou et al, 2008], no effects of EMF exposure were detected on brain physiology, and the visual, auditory and balance systems (Table 6). With the exception of critical flicker fusion frequency, which was recorded in two studies, each of the other endpoints was tested in only one study.…”
Section: Brain Physiology and The Sensory Systemmentioning
confidence: 99%
“…The authors concluded that EMF effects on the EEG are either non-existent or so prone to many other factors that they are difficult to demonstrate systematically. Bamiou et al [2008] studied the effects on auditory and vestibular functions of exposure from a modified handset capable of producing 882 MHz GSM and CW signals. No effects were observed from either sham, CW or GSM signals on the endpoints studied.…”
Section: Nervous System: Human Studiesmentioning
confidence: 99%
“…As for the vestibular part of the inner ear, short-term exposure to GSM signals did not induce nystagmus, which was measured with videooculography (VOG) Bamiou et al, 2008].…”
Section: Otoacoustic Emissionmentioning
confidence: 99%